Modus Ethical Categories as a Condition for the Emergence of Phraseological Semantics, their Application in Political Discourse - Klara Abisheva; Marzhan Akosheva; Gulbagira Ayupova; Aiman Nurgazina; Bulat Ayapbergenov; Assel Baikadamova (Space and Culture, India)
This article presents the results of a study of the formation processes of phraseological meanings considering cognitive-discursive conditions. Traditional and new (cognitive) approaches to the formation of phraseological semantics are analysed, and a method for the formation of phraseological meaning is proposed, namely the use of cognitive-discursive categories of state-mode. Modal categories contribute to a new moral and evaluative aspect of meaning. The research focuses on the representation of phraseological meanings in the formats of knowledge, concepts and ethical categories. The study aims to examine a new way of forming phraseological meanings based on the study of modus categories as a cognitive-discursive condition, as well as evaluative categorisation and the presentation of phraseological ethical knowledge in cognitive knowledge formats. An integrative methodological paradigm and a cognitive-semantic approach were applied in the study.   Cognitive semantics offers new principles for analysing phraseological units: equality of cognitive and communicative functions of language, interdisciplinarity, multifactoriality, anthropocentricity and multilevelness. When using them, phraseological units can be studied integratively, involving knowledge and methods from various sciences. Methods of modelling, contextual inference, evaluative categorisation, interpretation, cognitive-discursive analysis and associative experiment were also used. The study analyses various points of view on the nature of phraseological semantics, the cognitive-discursive and anthropological essence of phraseological meaning, and the possibility of phraseological units acting as knowledge formats.  The novelty of the work lies in the application of an integrative methodological paradigm based on cognitive-semantic and cognitive-discursive approaches, with an emphasis on the role of modus categories and evaluative categorisation in the formation of phraseological evaluative meaning in identifying the formats of phraseological knowledge, in applying a modus approach to the analysis of phraseological meanings.